Molecular detection of extended spectrum ?-lactamase producing Klebsiella pneumoniae from wild deer - KATTY HENDRIANA PRISCILIA RIWU; FEDIK ABDUL RANTAM; MUSTOFA HELMI EFFENDI; ASWIN RAFIF KHAIRULLAH; AGUS WIDODO; SHENDY CANADYA KJURNIAWAN; EMMANUEL NNABUIKE UGBO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Riwu KHP, Rantam FA, Effendi MH, Khairullah AR, Widodo A, Kurniawan SC, Ugbo EN. 2022. Molecular detection of extended spectrum ?-lactamase producing Klebsiella pneumoniae from wild deer. Biodiversitas 23: 4256-4262. Antimicrobial resistance (AMR) has become a severe threat worldwide and its remote cause remains unclear in most parts due to the global emergence of new resistance mechanisms by microorganisms. This research aimed to identify the presence of extended-spectrum ?-lactamase (ESBL) Klebsiella pneumoniae from wild deer feces in several places in East Java and East Nusa Tenggara. This study used 129 fresh feces samples collected from wild deer and analyzed for the presence of K. pneumoniae using standard microbiological techniques. An antibiotic sensitivity test was performed using Kirby-Bauer Disc Diffusion Method. The isolates were confirmed to the ESBL producer by double disk test and ESBL genes were identified by PCR. Nine samples (6.98%) were K. pneumoniae positive out of the 129 wild deer fresh feces. Among the nine K. pneumoniae isolates studied 3 (33.33%) were multidrug resistant, East Java (1 isolate) and East Nusa Tenggara (2 isolates). All the multidrug-resistant K. pneumoniae isolates were ESBL positive and also harbored blaTEM gene. The presence of MDR, and ESBL-producing K. pneumoniae isolates was confirmed in wild deer and this explained that wild deer should be considered a source of transmission of MDR and ESBL to public health.